Effects of guided collaboration on sixth graders' performance in logo programming - Lin, Janet Mei-Chuen; Lie, Yun-Lung; Ho, Rong-Guet; Li, Chia-Chen (2007 37th Annual Frontiers In Education Conference - Global Engineering: Knowledge Without Borders, Opportunities Without Passports, 2007)
In this study we investigated whether guided collaboration would enhance elementary school students' achievement in learning to program in MSWLogo. Ninty- four sixth graders were randomly assigned to the individual-learning group, the free-collaboration group or the guided-collaboration group. All students were taught to follow the problem-solving steps of analysis, design, coding, debugging, and reflection, but only students of the guided-collaboration group were provided a worksheet that aimed to force students to carry out all specified activities at each step. A statistical analysis of students' test scores showed that the guided-collaboration group significantly outperformed the other two groups. The differences among the low achievers of the three groups were especially significant, indicating that they had benefited the most from guided collaboration. It was also found that guided collaboration promoted meaningful discussions among students, which had contributed to their better understanding of programming concepts and problem-solving skills, and hence better test scores.